2021
DOI: 10.2147/cmar.s330429
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carcinoid Syndrome Symptoms Among Patients Receiving Telotristat Ethyl in US Clinical Practice: Findings from the TELEPRO-II Real-World Study

Abstract: Background Inadequately controlled symptoms incur a substantial burden on patients with neuroendocrine tumors and carcinoid syndrome (CS). The effectiveness of telotristat ethyl (TE) with a somatostatin analog for uncontrolled CS diarrhea has been demonstrated in clinical trials and observational studies. TELEPRO-II was a prospective observational study evaluating TE’s effectiveness in clinical practice over the first 3 months of treatment. Methods Patients initiating T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The real-world TELEPRO (2019) and TELEPRO-II (2021) studies reported a high baseline burden of CSD and CS symptoms for patients receiving SSAs only, and substantial improvements in patient-reported experience and outcomes after 3 months of TE in US clinical practice. 19 , 20 TELEPRO-II showed significant improvements in overall CS symptoms, daily bowel movement frequency, stool consistency, nausea, abdominal pain, urgency, and flushing as early as 1 month through 3 months of TE treatment. 20 After 3 months of TE, approximately half (52%) of patients in the TELEPRO study reported a reduction of ≥2 bowel movements per day.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The real-world TELEPRO (2019) and TELEPRO-II (2021) studies reported a high baseline burden of CSD and CS symptoms for patients receiving SSAs only, and substantial improvements in patient-reported experience and outcomes after 3 months of TE in US clinical practice. 19 , 20 TELEPRO-II showed significant improvements in overall CS symptoms, daily bowel movement frequency, stool consistency, nausea, abdominal pain, urgency, and flushing as early as 1 month through 3 months of TE treatment. 20 After 3 months of TE, approximately half (52%) of patients in the TELEPRO study reported a reduction of ≥2 bowel movements per day.…”
Section: Discussionmentioning
confidence: 95%
“… 19 , 20 TELEPRO-II showed significant improvements in overall CS symptoms, daily bowel movement frequency, stool consistency, nausea, abdominal pain, urgency, and flushing as early as 1 month through 3 months of TE treatment. 20 After 3 months of TE, approximately half (52%) of patients in the TELEPRO study reported a reduction of ≥2 bowel movements per day. 19 The majority of patients in the RELAX study reported less frequent bowel movements (82%) after 6 months of TE, underscoring the importance of continued follow-up and treatment adherence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Telotristat is an inhibitor of tryptophan hydroxylases (TPH 1 and TPH2) that limits serotonin biosynthesis and relieves manifestations of carcinoid syndrome. Telotristat together with a long-acting somatostatin analog is currently recommended for uncontrolled carcinoid syndrome diarrhea by the United States National Comprehensive Cancer Network (NCCN)[ 84 ].…”
Section: Managementmentioning
confidence: 99%
“…While in TPH1-deficient mice a protection from pulmonary arterial hypertension (PAH), , inflammation, nonalcoholic steatohepatitis, , and irritable bowel disease was observed, TPH2-deficient mice suffered from neuronal dysfunction such as increased aggressive behavior, , altered anxiety, and social deficit. , Moreover, the overexpression of TPH1 in neuroendocrine tumors in patients with carcinoid syndrome (CS), results in an increased secretion of serotonin into the bloodstream, causing severe side effects like skin flushing, diarrhea, shortness of breath, and rapid heart rate . In a proof of concept clinical study, Telotristat Etiprate (Xermelo) as new TPH1 inhibitor received fast track status ( 1.1 in Figure ) for the treatment of patients suffering from CS in 2017. , In addition, the companies Altavant Sciences GmbH and Actelion Pharmaceuticals, Ltd. described novel TPH inhibitors ( 2.1 and rac- 3 in Figure ) to treat diseases related to high levels of serotonin. , Currently, Enzyvant Therapeutics GmbH is conducting a clinical phase II study (ELEVATE 2, NCT04712669) with Rodatristat Ethyl 2.1 in patients suffering from PAH . The activated inhibitors 1.2 and 2.2 mainly cover the substrate-binding site of tryptophan, with the amino acid headgroup forming hydrogen bonds with Arg-257, whereas the inhibitor rac- 3 occupies both binding sites of the substrate and the pterin cosubstrate.…”
Section: Introductionmentioning
confidence: 99%